Embryonic ethanol exposure disrupts craniofacial neuromuscular integration in zebrafish larvae - Ghosal, Ritika; Borrego-Soto, Gissela; Eberhart, Johann K. (Frontiers in Physiology, 2023)
Forming a vertebrate head involves the meticulous integration of multiple tissue types during development. Prenatal alcohol exposure is known to cause a variety of birth defects, especially to tissues in the vertebrate head. However, a systematic analysis of coordinated defects across tissues in the head is lacking. Here, we delineate the effects of ethanol on individual tissue types and their integration during craniofacial development. We found that exposure to 1% ethanol induced ectopic cranial muscle & nerve defects with only slight effects on skeletal pattern. Ectopic muscles were, however, unaccompanied by ectopic tendons and could be partially rescued by anesthetizing the larvae before muscle fibers appeared. This finding suggests that the ectopic muscles result from fiber detachment and are not due to an underlying muscle patterning defect. Interestingly, immobilization did not rescue the nerve defects, thus ethanol has an independent effect on each tissue even though they are linked in developmental time & space. Time-course experiments demonstrated an increase in nerve defects with ethanol exposure between 48hpf-4dpf. Time-lapse imaging confirmed the absence of nerve pathfinding or misrouting defects until 48hpf. These results indicate that ethanol-induced nerve defects occur at the time of muscle innervation and after musculoskeletal patterning. Further, we investigated the effect of ethanol on the neuromuscular junctions of the craniofacial muscles and found a reduced number of postsynaptic receptors with no significant effect on the presynaptic terminals. Our study shows that craniofacial soft tissues are particularly susceptible to ethanol-induced damage and that these defects appear independent from one another. Thus, the effects of ethanol on the vertebrate head appear highly pleiotropic.